Linguistic Features Of The 2016 United States Presidential Election Debates - Bùi Vân Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis is aimed at examining linguistic features of Presidential election debates. The data for analysis in this thesis are the three debates of the 2016 United States Presidential debates with more than 50.000 words. These samples were collected from several official websites from the United States. The thesis was carried out based on a combination of a variety of methods such as descriptive, qualitative and quantitative. The thesis focused on analyzing linguistic features of presidential debates in terms of syntactic structures, lexical choices and cohesive devices. The thesis attempts to find out some typical linguistic features of the 2016 US Presidential debates in the view of Quirk (1985) and Halliday and Hassan (1976) in their books. The findings of this study show that the phrases, relative clauses and passive voice are commonly used Presidential debates with the aim at getting listener‘s attention. In addition, the use of intensifiers, descriptive adjective, compounds make the debates clearer and more persuasive. Besides, grammatical and lexical cohesive devices help hold the text together and make people easier to understand what the speakers want to convey. It is hoped that the results of this thesis can be beneficial for the teaching and learning of English language. This thesis may also be helpful for the readers in getting the detailed information from the speeches of the two candidates in the US Presidential debates.